Esegesi umanistica alle Silvae di Stazio: Parrasio - ABBAMONTE, Giancarlo (Euphrosyne, 2003)
Abstract The 15th century fortune of Statius’ Silvae has been studied mostly for the textual transmission of this work rather than for its fortune in the humanistic culture and poetry. The present work focusses on the materials on Silvae, which the Humanist Aulus Janus Parrhasius (1470-1521) scattered in many manuscripts during his life, and establishes a relationship among Parrhasius’ comments and those previously written by Domitius Calderini (1475) and Politianus (ca 1481). In fact, they constitute the main sources of Parrhasius’ interpretation of Statius’ Silvae.